2014
DOI: 10.5005/jp-journals-10023-1081
|View full text |Cite
|
Sign up to set email alerts
|

Voice Analysis in Individuals with Chronic Obstructive Pulmonary Disease

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a respiratory condition that can affect voice as respiration is the source for voice production. There are very few studies available on the analysis of voice in individuals with COPD (asthma, chronic bronchitis and emphysema). Purpose of the study The aim of this study was to analyze the acoustic and perceptual characteristics of voice in individuals with COPD. Method The study followed a comparative cross-sectional study design. Sixty-four partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Traditionally patients are asked to say 'Ee' in egophony which transformed to 'A' for patients suffering from respiratory diseases [33,36]. However, the usage of other characters are also common, and various previous works [8,35,41] utilized different types of vocal sounds to diagnose COPD and Asthma patients. Dogan et al, [8] used 's' and 'z' phonate and showed that the maximum phonation time is significantly shorter for asthma patients.…”
Section: Vowel Sound For Respiratory Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally patients are asked to say 'Ee' in egophony which transformed to 'A' for patients suffering from respiratory diseases [33,36]. However, the usage of other characters are also common, and various previous works [8,35,41] utilized different types of vocal sounds to diagnose COPD and Asthma patients. Dogan et al, [8] used 's' and 'z' phonate and showed that the maximum phonation time is significantly shorter for asthma patients.…”
Section: Vowel Sound For Respiratory Assessmentmentioning
confidence: 99%
“…Dogan et al, [8] used 's' and 'z' phonate and showed that the maximum phonation time is significantly shorter for asthma patients. Shastri et al, [35] used 'Aaaa... ' vowel and performed voice analysis on the data collected from 64 participants (32 COPD patients and 32 healthy participants). Their result also showed a significant difference between healthy participants and COPD patients on various acoustic measures, including lower fundamental frequency, reduced frequency range, increased pitch, amplitude perturbation measures, and increased noise measures.…”
Section: Vowel Sound For Respiratory Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic speech features are affected in patients suffering from respiratory diseases such as chronic obstructive pulmonary disease (COPD) or asthma [1][2][3], especially fundamental frequency (f0) and voice quality parameters. Some works have reported relevant correlations between f0 and voice quality parameters with the smoking index and the forced expiratory volume in one second (FEV 1 ) and the asthma degree [1,2], and increased voice quality parameters or breath sounds in patients with pneumonia and COPD [4][5][6][7], so that relevant differences appear between healthy and COPD subjects in acoustic and perceptual voice parameters [8]. Voice changes are also encountered in respiratory sounds in infants [9], bronchodilator response effects in asthma tracheal sounds [10][11][12], obstructive sleep apnea [13], and voice rise in dyspnea [14].…”
Section: Introductionmentioning
confidence: 99%
“…These include but are not restricted to Sicca syndrome [ 10 ], dry mouth syndrome [ 11 ] and body dehydration [ 12 ], hormonal alterations linked to pubertal [ 13 ], menopausal [ 14 ] and andropausal [ 15 ] status and acromegaly [ 16 ], cardio-vocal syndrome [ 17 ], respiratory disorders (e.g. chronic obstructive pulmonary disease [ 18 ] and asthma [ 19 ]), gastrointestinal reflux [ 20 ], autoimmune diseases such as rheumatic arthritis [ 21 ] and Sjögren’s syndrome [ 22 ], systemic lupus erythematosus [ 23 ], amyloidosis [ 24 ], cystic fibrosis [ 25 ], endocrinologic disorders such thyroid dysfunction [ 26 , 27 ] and anorexia nervosa [ 28 30 ], underweight versus overweight and obesity [ 31 , 32 ], and diabetes [ 33 ]. Table 2 highlights corresponding laryngeal symptoms.…”
Section: Introductionmentioning
confidence: 99%